Harbour Seal Decline - vital rates and drivers : Report to Scottish Government MMSS/002/15 - Arso Civil, Monica; Smout, Sophie Caroline; Duck, Callan David; Morris, Christopher; Onoufriou, Joseph; Thompson, David; Brownlow, Andrew; Davison, Nicholas; Cummings, Caroline; Pomeroy, Patrick; McConnell, Bernie J; Hall, Ailsa Jane (SMRU, 2017)
Numbers of harbour seals (Phoca vitulina) have dramatically declined in several regions of the north and east of Scotland, while numbers have remained stable or have increased in regions on the west coast. For any management and mitigation plans to address this situation, the relative contribution of various factors in the decline of harbour seals in Scotland needs to be identified, understood and assessed. Potential drivers of the decline include changes in prey quality and/or availability, increasing grey seal population size which may be influencing harbour seal populations through direct predation or competition for prey resources, and the occurrence and exposure of seals to toxins from harmful algae. Previous work by Matthiopoulos et al. (2014) and Caillat and Smout (2015) developed and fitted an age-structured population model to data from the well-studied subpopulation of harbour seals in Loch Fleet (Moray Firth), to evaluate the contributions of different potential proximate causes to the observed decline. After reviewing the existing software, this model has been re-coded directly into R, a framework that will allow for future development and maintenance, and has been designed to be adapted to different model structures and future data sets. Preliminary results are consistent with those obtained from the original OpenBUGS modelling. Future work will have as its key objective the identification of the important drivers of population change in harbour seals, from those being studied as listed above. Temporal and spatial variation in these drivers will be incorporated into the population model. Harbour seal haulout sites located in different regions of Scotland were visited in the spring and the summer of 2015 to collect information on their suitability for long-term monitoring of harbour seal populations, including their suitability for live captures, scat sampling, aerial and ground survey counts during pupping and moulting and photo-identification. This will allow empirical data to be collected and ...